KOMUNITAS SERANGGA DAN VEGETASI PENUTUP TANAH PADA LAHAN SAWAH TADAH HUJAN DI KUTAI KARTANEGARA: EFEK VARIASI KETINGGIAN TEMPAT: INSECT COMMUNITIES AND GROUND COVER VEGETATION IN RAINFED PADDY FIELDS OF KUTAI KARTANEGARA: THE EFFECT OF ALTITUDE VARIATIONS - Putri, Dina Hayati; Nurmianti, Nurmianti; Hariani, Nova; Budiman, Budiman (AgriPeat, 2025)
Variations in altitude create significant differences in environmental conditions, such as temperature, humidity, and nutrient availability, which profoundly affect the structure of vegetation and insect communities. These variations influence biodiversity levels and the patterns of interactions between vegetation and insects within ecosystems. Therefore, this descriptive exploratory study was conducted to analyze the diversity of ground-dwelling insect communities and the structure of ground cover vegetation in Gedagai Putih rice fields across different altitudinal gradients. Insect sampling was carried out using the pitfall trap method, while vegetation observations were conducted using 60 cm x 80 cm plots. The results of the study indicate that altitudinal variations significantly influence the composition and dominance of insect and ground cover vegetation species. The highest dominance level of insect Genus was observed for Entomobrya (IVI = 67.48) in Zone III (300 m a.s.l), while the lowest dominance was recorded for Alydus and Leptocorisa (IVI = 1.55) in Zone I (108 m a.s.l). For plant species, the highest dominance was observed in Paspalum conjugatum (IVI = 133), while the lowest dominance was recorded for Alocasia sp (IVI = 7) in Zone I.